СHAOTIC COMMUTATING WITH THE DUNKL DIFFERENTIATION LINEAR OPERATORS ON THE SPACE OF ANALYTIC FUNCTIONS - A.V. BRATISHCHEV (Advanced Engineering Research, 2009)
We give representation of linea continuous operator, commutating with Dankle differentiation. These operators turn out to be chaotic and hypercyclic.